Análise geoambiental das bacias hidrográficas federais do Cerrado Mineiro - Silva, Mirna Karla Amorim da (2009)
The general objective of this study is to map and analyze the environmental characteristics related to: hypsometry, clinography, soils and land use and natural vegetation of river basins from Cerrado s biome in the state of Minas Gerais, to contribute to an environmental study with increasing depth in important areas of our ecosystem, aiming the preservation and sustainable use of its land. The studied area lies between the geographical coordinates of 14º 13' and 22 º 54 'south latitude and 39º 51' and 51º 02' longitude west of Greenwich, covering 57% of the state of Minas Gerais. To accomplish this research we used georeferenced vector data (boundary, hydrography and road network), in the scale of 1:1.000.000 (IBGE), ETM + images / Landsat (2002), Digital Elevation Model (DEM) of the State of Minas Gerais (SRTM) and soils classification data from IBGE and EMBRAPA (2001). The vector data for class distribution of natural vegetation and human use were obstained from the Project for Conservation and Sustainable Use of Brazilian Biological Diversity (PROBIO), the data for soils classification, from a compilation of studies conducted by IBGE and available on the Internet, and, finally, clinography and hypsometric data, as the delimitation of geoenvironmental units in the studied area, were prepared from DEM s of the State of Minas Gerais. Using the softwares ArcView, Idrisi, and Cartalinx Arcgis, we prepared the cartographic basis and the thematic maps: federal basins, geographic location, hypsometry, clinography, soils, land use and vegetation cover and natural geoenvironmental units of the studied area, for further analysis related to it. The area of Cerrado has been environmentally threatened and the data presented along the research show the stage of conservation/use of the basins studied in the Cerrado of Minas Gerais. The percentage of human use and natural vegetation cover, respectively, of the studied basins are: basin of Rio Doce (44.23% and 55.75%), Rio Grande basin (73.38% and 21.40%), Jequitinhonha river basin (27.14% and 72.86%), Paranaíba river basin (70.82% and 27.22%), Pardo river basin (35.56% and 64.43%) and São Francisco River basin (40.38% and 58.86%). These and other results of this study show that, although it is still present in greater proportion in most of the basins studied, the areas of remaining natural vegetation in the Cerrado of Minas Gerais are fragmented, and it can reduce the protection of biodiversity in the area of this biome considered as a priority area for conservation for the preservation of its species. The data generated by the diagnosis of the basins studied are relevant to the formation of a database of environmental variables considered in each thematic mapping prepared, and the intersection among this information to analyze the interaction of all elements involved in the landscape dynamics. Therefore, the environmental diagnosis of the studied area can promote interventions and corrective or preventive conservation of the natural environment and natural resources through the use of geographic information systems (GIS), Remote Sensing and Geoprocessing as a whole, as supportive tools for the management of natural environments decision. The use of existing geotechnologies was an effective and essential tool for this purpose. Therefore, this research is placed as a start for studies, discussions and future actions, including other environmental variables and socio-economic variables of the Cerrado area of Minas Gerais.